Aktor społeczny i rzeczywistość społeczna. Zapomniany potencjał socjofenomenologii - Chojnacki, Marek (Kultura i Społeczeństwo, 2007)
Have the currently most important proponents of sociological theory adopted Alfred Schutz’s thesis concerning the proximity of the views of society and of those who research it and are they in a position to construct a theory which will not conceal social reality by returning to the positivistic and functionalistic models. Since doubts exist in this respect, this paper suggests a return to the material stage of the development of the theory of social life created by the interpretation of Schutz’s concept — especially the ethnomethodology inspired by it. When considering certain aspects of the history of ethnomethodology — especially its progress into conversational analysis — which are regarded as research into areas of interaction which are banal, positivistically understood, isolated and unrelated to the whole, I find an example of a meaning of socio-phenomenology in the “constructivistic” theories of Melvin Pollner and Steve Woolgar which allows the various, notable actions of actors to be treated as deeds which establish and maintain the fundamental and ultimate versions of the world and which allow individual deeds to be treated as “documents” and symptoms of the way in which the actors understand the whole social system. This concept allows for a return to the core of Schultz’s proposal which was labelled by Harold Garfinkel as “accountability”.